Learning Media for Introducing the Khulafaur Rasyidin Using the Multimedia Development Life Cycle Method - Lubis, Said Alkhudri (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The use of Augmented Reality (AR) technology in the field of education is rapidly advancing, including in the teaching of Islamic history. This study aims to design and develop an interactive and engaging AR-based learning medium for introducing the Khulafaur Rasyidin, the first four caliphs in Islamic history. The Multimedia Development Life Cycle (MDLC) method is employed as the development framework, consisting of six stages: concept, design, material collection, development, testing, and distribution. Through this learning medium, students can learn about the history of the Khulafaur Rasyidin in a more interactive and visual manner using AR technology. Each caliph is introduced with comprehensive information in the form of text, audio, and 3D models that can be viewed through mobile devices. Based on trials conducted with 15 respondents, 95.96% agreed, 4.20% were uncertain, and 0% disagreed. This indicates that this AR-based learning medium significantly enhances students' understanding compared to conventional learning methods. The use of AR technology combined with the MDLC development approach has proven to be effective in creating an engaging, interactive, and easy-to-understand learning experience. This medium can serve as an innovative solution for introducing the history of the Khulafaur Rasyidin to students across various educational levels.